Habitação de interesse social e parque urbano no igarapé do Quarenta - Targino, Ismael da Silva (Brasil, 2022)
Manaus is the capital of the state of Amazonas, has undergone several transformations in the process of urbanization of the city due to two moments, being them, the era of rubber and the creation of the Manaus Free Trade Zone. These moments brought a great impact on the urbanization of the city as there was a great leap in the economy place, many people migrated to the city in search of opportunities, resulting in the emergence of irregular housing on the outskirts, including in the banks of the city's streams, such as stilt houses. Manaus continues to grow and the problem of lack of housing still persists in its territory, although many areas of irregular occupation had become consolidated neighborhoods, therefore, this This work presents a project for the reintegration of families living on the of the city's streams, who live irregularly and at risk, specifically in the forty stream, which is the target of the intervention, seeking the recovery of nature and the natural state of the stream and create spaces for socialization and connection with the stream. For this to occur, a study is carried out history of the emergence of neighborhoods close to the forty stream and an analysis history of occupation on the banks of the stream over time, combined with the diagnosis of uses and occupations in the territory and how the stilt house is configured and influence in space, resulting in an urban social housing project that reintegrates residents at risk to the urban environment by supplying their basic necessities, plus the revitalized edge with an element of connection, with spaces for social interaction and public spaces between dwellings.